The Association Between Illicit Drug Use and the Duration of Renal Replacement Therapy in Patients With Acute Kidney Injury From Severe Rhabdomyolysis - Lim, Andy K. H.; Azraai, Meor; Pham, Jeanette H.; Looi, Wenye F.; Bennett, Caitriona (Frontiers in Medicine, 2020)
Background and aims: Acute kidney injury is a known complication of severe rhabdomyolysis. In patients who present to hospital with rhabdomyolysis, illicit drug use is associated with a higher risk of acute kidney injury needing renal replacement therapy (RRT), independent of the peak serum creatine kinase level. The aim of this study was to assess if RRT duration and renal outcomes were also worse in illicit drug use-associated rhabdomyolysis. Methods: We conducted a cohort study of adult patients who presented to Monash Health (Jan 2011 to June 2020) with rhabdomyolysis and required RRT. Patients with isolated myocardial injury and cardiac arrest were excluded. We used survival analysis to examine the time to RRT independence, utilizing the Fine-Gray competing risks regression and death as the competing event. A subdistribution hazard ratio (SHR) <1.0 represents a relatively greater duration of RRT and a worse outcome. Results: We included 101 patients with a mean age of 58 years, of which 17% were cases associated with illicit drug use. The median peak creatine kinase level was 5473 U/L (interquartile range, 1795-17051 U/L). Most patients (79%) initiated RRT within 72 hours of admission, at a median serum creatinine of 537 µmol/L (interquartile range, 332–749 µmol/L). In the competing risks analysis, the estimated SHR was 1.48 (95% CI: 0.78-2.84, P = 0.23) for illicit drug use, 0.87 (95% CI: 0.76-0.99, P = 0.041) for the log-transformed peak creatine kinase, and 0.41 (95% CI: 0.25-0.67, P <0.001) for sepsis. A 50% cumulative incidence of RRT independence occurred at 11 days (95% CI: 8-16 days). Only 5% of patients remained on RRT at 3 months. Conclusion: In rhabdomyolysis-associated acute kidney injury, it is unlikely that patients with illicit drug use-associated rhabdomyolysis require a longer duration of RRT compared to patients with rhabdomyolysis from other causes.